Cornel West's Pragmatic Understanding of America. (January 2017) - Conlon, James
Cornel West's intellectual performance does not fit neatly into the usual academic categories. One of his goals from the beginning, as he himself repeatedly attests, has been "to examine critically the soul of American civilization." This article summarizes his understanding of America and explores some of the ways it has been articulated. It first examines some specific ways that West finds American civilization distinctive in both its institutions and attitudes. It then offers his analysis of what American citizenship means, the ethical commitments inherent in its founding vision, and any contemporary allegiance to it. Finally, it examines the significance West gives to blues and jazz in American life. Since they are, he argues, America's most distinctive artistic creations, they have played an important role in expressing its democratic soul. The overall understanding of America that emerges from West's prodigious and multifaceted work provides not only interesting possibilities for American self-reflection but also directions for political change.